Candida auris: a worrisome, globally emerging pathogen. Issue 9 (2nd September 2017) - Navalkele, Bhagyashri D.; Revankar, Sanjay; Chandrasekar, Pranatharthi
ABSTRACT: Introduction : Candida auris is a recently discovered, rapidly emerging fungal pathogen. Infections due to C. auris are hospital-acquired, multidrug resistant and associated with high mortality. Areas covered : This review highlights epidemiology, pathogenesis, microbiological characteristics, clinical presentation, diagnostic challenges and treatment options of C. auris infections. Infection prevention measures to prevent spread of C. auris and special measures during an outbreak situation have also been reviewed. Expert commentary : Rapid emergence of hospital onset C. auris is worrisome. Early diagnosis of C. auris is essential for better outcomes and the implementation of infection prevention measures. Lack of widespread awareness, absence of general availability of diagnostic testing methods, and limited options for treatment of C. auris infections make it a difficult-to-treat pathogen. Further studies are needed for better understanding of this emerging pathogen.